Channel monitored channel duplexer for optimization of bidirectional passive optical network - Taibin, Y. (Penerbit UTM Press, 2016)
Method of optimizing the optical network transmission in access network has been investigated in many years. Unidirectional optical transmission system is the earliest method of delivering the information. In recent years, bidirectional optical transmission system is the most popular network and shall be the first right of refusal to deploy nowadays. It is justify enough by the massive deployment of the popular state-of-the-art network named Passive Optical Network (PON) in Fiber To The Home (FTTH) technologies. Combining 3 wavelengths includes (1) 1310nm, (2) 1490nm, and (3) 1550nm within a fiber is the method used on Gigabit Capable Passive Optical Network (GPON) or Gigabit Ethernet Passive Optical Network (GEPON/EPON). Combining 2 different wavelengths for uplink and downlink on Small Form Pluggable (SFP) lasers also has been a method used to optimized and saved the fiber infrastructure. Compared those techniques, the research optimization focusing on introducing a passive optical duplexer that combined the same wavelength from both end with the element of monitoring via different wavelength to confirm the network availability. In the design, a unidirectional converter able to operate at a nominal 1310nm or 1550nm windows shall be demonstrated up to 10Gbps Ethernet signal.